Establishment of reprographic center in Barangay Sampaloc, Tanay, Rizal - Fernandez, Maria Teresa B.; Nobleza, Emma N.; Rull, Boots Layka B.; Silverio, Rey Ann S.; Dizon, Ailey B. (2016)
The proponents oblige to manage the daily transaction and accommodate with the costumers and other operational matters. The opening of the center will be scheduled on the first week of January 2017.
Feasibility studies
Include bibliographical references.
Keywords: Copying services -- Philippines -- Rizal; Feasibility studies